Anti-metastatic potential of cacao, cassava, and cotton plant leaf extracts via inhibition of cancer cell migration - SHARDAE, GUICO (Archīum Ateneo, 2016)
Around 90% of deaths in cancer are due to metastasis-the spread of cancer cells throughout the body. Matrix metalloproteinase 9 (MMP-9) plays a key role in this process by degrading components of the basement membrane (BM) and extracellular matrix (ECM).